IMPLEMENTATION OF BLOCKCHAIN TECHNOLOGY IN THE BANKING SECTOR (Pakistan Journal of Scientific Research, 2023)
Traditional Banking networks have been implemented worldwide. However, there are numerous security threats to these banking networks. Due to these threats, many banks have not been able to establish a sense of security among their customers. Every bank has different threats based on multiple factors such as network configuration, region, customer base, etc. Improving the security of banking networks worldwide is the need of the hour. For this purpose, the best solution to overcome all the existing security challenges of the banking networks worldwide is to upgrade them to blockchain networks. As of today, Blockchain is the best alternative to conventional banking networks. Despite its security challenges, it can be considered the best solution to overcome this global issue. This paper, first of all, highlights the significant issues in transactions in the banking sector. These issues include security and attack risks, and the involvement of multiple stakeholders. Then further, this paper proposes a new algorithm based on blockchain technology to overcome these issues. Additionally, the simulation results showing the transaction between 2 nodes are mentioned.
Keywords: Banking; Blockchain; data security